Supply chain management best practices - Blanchard, David, 1958- (Wiley, 2021)
"Supply chain management is a topic of great interest in businesses today with new technology and environmental issues, along with the need to reduce costs. Add to this the fact that supply chain professionals have been entrusted with managing nearly $1 trillion worth of logistics costs every year, representing close to 8.5% of the total U.S. gross domestic product and a clearer picture emerges of what is at stake and what can be gained by running a best-in-class supply chain"--